The effect of biochar amendment on the health, greenhouse gas emission, and climate change resilience of soil in a temperate agroecosystem - Jiang, Runshan (Will) (University of Waterloo, 2019)
Biochar has been a successful soil amendment in tropical agriculture for thousands of years. Biochar’s intrinsic chemical and physical properties benefit agriculture in terms of soil health, environmental pollution, and crop productivity. The effect of biochar as a soil amendment in temperate agriculture faces unique challenges and is still in its infancy. The objectives of this study were to determine the effect of a wood-biochar in a temperate agricultural soil in terms of soil health, greenhouse gas (GHG) emissions, and resilience against warming and CO2 fertilization. This study consisted of three triplicated soil treatments: 6t/ha poultry manure and 135 kg/ha urea-N fertilizer (MN), 3t/ha poultry manure and 3t/ha biochar (MB), and 3 t/ha poultry manure, 135 kg/ha urea-N fertilizer, and 3t/ha biochar (MNB). The field study found a significantly greater fraction of stable macroaggregates in MB than MN and MNB (p=0.040), lower NH4+-N in MB than MN and MNB (p < 0.001), and higher soil microbial biomass carbon in MNB than MN and MB (p = 0.002). The temporal soil GHG emission study found significantly lower CO2 and trends in lower N2O (not significant) emissions with biochar amendment (p = 0.031). However, the seasonal factor (e.g. soil moisture) had a greater influence on soil GHG emission. The climate change resilience study introduced climate condition as a second fixed factor including: ambient (AMB), elevated temperature (TEMP), CO2 fertilization (fCO2), and elevated temperature plus CO2 fertilization (fCO2×TEMP). Results showed biochar behaved independently of the climate condition factor for vast majority of soil and soybean characteristics. MNB responded poorly compared to MN and MB in many soil and plant characteristics suggesting conflicting urea-biochar interactions. Soybeans matured quicker under warming effect but developed abnormal physical traits. Findings from these studies suggest biochar can be a valuable implementation to temperate soil to improve soil health and mitigate environmental stress that leads to and results from climate change.
Keywords: biochar; soil; greenhouse gas; temperate; agriculture; climate change